STUDENTS' MATHEMATICAL COMMUNICATION SKILLS REVIEWED FROM SELF-CONFIDENCE THROUGH APPROACH PROBLEM-BASED LEARNING (PBL) - Lubis, Risa Nursamsih; Hakim, Lukman El; Aziz, Tian Abdul (Tesseract: International Journal of Geometry and Applied Mathematics, 2023)
One of the abilities that is very important to pay attention to in learning mathematics is students' mathematical communication skills. In addition to mathematical communication abilities, other aspects must be considered and support students' success in mathematics, including self-confidence. Students with high self-confidence can understand and express their ideas or ideas in language and mathematical symbols to convey information or opinions through speech or writing. This study aims to provide an overview of students' Mathematical Communication Ability in terms of Self-confidence through a Problem Based Learning (PBL) Approach. The method used is descriptive, describing the results of a literature review of at least 25 relevant articles. The results of this study are that there is a positive relationship between students' self-confidence and mathematical communication abilities and the Problem Based Learning Approach is effective in improving students' mathematical communication skills and self-confidence